Association Between Chronic Health Conditions and Quality of Life in Rural Teachers - Lizana, Pablo A.; Vega-Fernandez, Gustavo; Lera, Lydia (Frontiers in Psychology, 2020)
The school teacher profession has been reported to be associated with an increased rate of health problems that can affect the quality of life (QoL) of teachers. However, there is little information about rural teachers. Objective. To investigate the associations of obesity, abdominal obesity and hypertension with the perception of QoL in rural teachers. Materials and methods. This cross-sectional study included a representative sample of teachers from eight rural schools in the Valparaíso region of Chile. Obesity was evaluated by the percentages of fat mass (%FM) and abdominal obesity, and hypertension was recorded. The Short Form-36 Health Survey was administered to subjects to evaluate QoL. A logistic regression adjusted for age and sex was used to associate chronic health conditions with QoL. Results. Eighty-five percent of teachers presented abdominal obesity, 56% presented obesity evaluated by % FM and 33% presented hypertension. Thirty percent of teachers in the ≥ 45-year-old age group presented all three chronic conditions simultaneously. Teachers presenting abdominal obesity in the ≤ 44-year-old age group had lower scores in the mental health component (MCS) (p < 0.05) of the survey than the teachers in the ≥ 45-year-old age group. In addition, teachers in the ≤ 44-year-old age group who presented obesity scored lower in the MCS than those in the same age group without obesity (p = 0.004). Age ≥ 45 years had a significant association with the simultaneous presence of all three conditions (OR 18.5, 95% CI: 2.538 - 134.57) and a decreased MCS (OR 7.9, 95% CI: 1.264 – 49.422). Conclusions. Rural teachers present more chronic conditions as they age, and a combination of conditions affects the mental health of teachers. This suggests that resources must be made available to detect and manage the chronic health conditions of rural teachers.